Increasing Management Effectiveness of Non-Formal Education Management in Community Learning Activity Centers - Lausa, Ferlyn Joy Lausa Diaz; Rahman, Afandi; Puspitasari, Savira Widya; Abdurochman, Abdurochman (Jurnal Pendidikan Nonformal, 2024)
Non-Formal Education is a solution for children and adults who have dropped out of school. Apart from that, with Non-Formal Education, educational services can serve anyone, because obtaining education, science and knowledge can be done in formal or non-formal ways. The education management process includes planning, organizing, implementing, monitoring and evaluating. Through good planning, it is hoped that PKBM can become a truly effective forum for community empowerment, so that it can improve the quality of life of the community as expected and ultimately be able to improve the quality of human resources as a whole. The general aim of this research is to determine the effectiveness of PKBM management. The specific aim of this research is to determine the effectiveness of planning, organizing, implementing, controlling and evaluating PKBM. This research method is evaluative, collecting data through interviews, observation and documentation. The results of this research show that the effectiveness of management in PKBM Sejahtera Insan Indonesia in East Barito Regency, South Kalimantan is effective, both from planning analysis, organization, implementation, control and evaluation due to management. In accordance with PKBM management standards and based on analysis standards for PKBM Sejahtera Insan Indonesia in East Barito Regency, South Kalimantan, it received a score of 100%, which means all aspects are effective. The management carried out at PKBM Sejahtera Insan Indonesia is running according to initial planning.